KRITIK EKONOMI KONVENSIONAL DAN SOLUSI EKONOMI ISLAM - Tanjung, Hendri (Hunafa: Jurnal Studia Islamika, 2014)
Purpose of this study is to review some critics to conventional economics in some aspects, i.e., theory, culture, ethics, and system.Â  At the same time this study aims at searching some solutions for healthy economics (Islamic Economics).Â  The data used in this study are Law No. 3 of 2006 on religious courts, Law No. 2 of 1992 on insurance, data from National Zakat Board, and data from Bank Indonesia.Â  The methodology used is qualitative method using descriptive analysis and literature review.Â  This study concludes that there have been many criticisms of the conventional economic by conventional economist as well as by experts of Islamic economics. To that end, there should be Islamic solution in the economic field.Â  Solution of Islamic economics can be done by Islamic market integration strategy into economic activities through zakat, waqaf, Islamic social security, Islamic justice system and Islamic financial institutions ( Islamic Banks, TakÄful, and Rahn).Â Kata Kunci : kritik, ekonomi konvensional, ekonomi Islam.